Prophecy Of Playing Ability Among Inter-Collegiate Volleyball Players Pertaining To A Few Anthropometric Variables - Vignesh.P*, Dr.B.S.Sha Yin Sha, Dr.M.Suresh Kumar (South Eastern European Journal of Public Health, 2025)
The study's goal was to predict college-level male volleyball players' skill level based on a few chosen anthropometric factors. Three hundred and twelve male volleyball players, ages 18 to 25, were chosen at random from different colleges in Tamilnadu state, India, in order to accomplish the goal. Only those who played for their respective collegiate teams were included in the study, and the subjects had played volleyball for at least three years prior. In this study, the volleyball playing ability was predicted with the help of anthropometrical variables namely – Body Weight, Thigh Girth, Calf Girth, Hand length and Chest girth. Three certified volleyball coaches evaluated the playing ability, which was defined as the performance factor, subjectively. Five independent variables and one dependent variable, the volleyball players' skill made up the current study. As detailed below, statistical analysis was performed on the collected data. Multiple regressions and the Pearson product moment correlation were also employed. On the basis of results, it was concluded that anthropometrical characteristics in the form of hand length, calf girth and thigh girth are major contributors in playing ability of Inter-collegiate volleyball players.